ANTIOSTEOPOROTIC DRUG PREFERENCES IN PHYSICAL MEDICINE AND REHABILITATION CLINIC - DELEN, veysel; AKÇALI, Remziye (Göbeklitepe Medical Science Journal, 2024)
Osteoporosis (OP) is a systemic disease characterized by deterioration in the microstructure of bone tissue and low bone mass, resulting in increased bone fragility and increased likelihood of fracture. In this study conducted in the PTR department of Harran University Hospital, the files of patients who applied to our outpatient clinic between January 2022 and January 2023 were evaluated retrospectively. The patients were divided into two groups according to gender and age groups. The drug treatments received by the patients were evaluated according to gender and age groups. In our study, oral bisphosphonates were the most frequently reported, followed by denosumab. Alendronate was the most frequently reported drug in both men and women. OP is an important health problem that concerns both individuals and the entire society. Therefore, every individual in society should be informed about OP.